2007
DOI: 10.1016/j.abb.2007.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the human cathepsin E gene by the constitutive androstane receptor

Abstract: Cathepsin E (CTSE) is an aspartic protease that has been linked to antigen processing and innate immunity. Elevated levels of CTSE expression have also been associated with several forms of cancer, including carcinomas exhibiting highly invasive character. In this study, we performed DNA microarray experiments, together with quantitative reverse transcriptase PCR analyses and enzymatic activity determinations to identify human CTSE as a novel target gene for regulation by the constitutive androstane receptor (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
(59 reference statements)
0
3
0
Order By: Relevance
“…Recent evidence has demonstrated that the A variety of intra-and extracellular proteases, including aspartic proteinases and cysteine cathepsins, are highly up-regulated in certain types of cancers (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). In addition, there is a change in the localization of the endolysosomal proteases to extracellular spaces.…”
Section: Cathepsin E and Cancermentioning
confidence: 99%
See 1 more Smart Citation
“…Recent evidence has demonstrated that the A variety of intra-and extracellular proteases, including aspartic proteinases and cysteine cathepsins, are highly up-regulated in certain types of cancers (69)(70)(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84). In addition, there is a change in the localization of the endolysosomal proteases to extracellular spaces.…”
Section: Cathepsin E and Cancermentioning
confidence: 99%
“…The proteolytic activity of extracellular aspartic and cysteine cathepsins has long been associated with many types and stages of cancer (73)(74)(75)(76)(77)(81)(82)(83)(84)(85)(86)(87). Cathepsin E is also known to be up-regulated and secreted in several forms of cancer and thus suggests their clinical utility as a potential biomarker for these cancers (69,(71)(72)(73)(74)(75)(76)(77)(78)(79)(80)88). However, the clinical significance of the increased cathepsin E expression in carcinogenesis has been controversial.…”
Section: Cathepsin E and Cancermentioning
confidence: 99%
“…Subsequent to their activation, both CAR and the pregnane X receptor (PXR) function as transcriptional regulators of genes participating in hepatic biotransformation and drug transport (Chang and Waxman, 2006), affecting the dispositional fate of many drugs (Wei et al, 2000), chemical carcinogens (Xie et al, 2003) as well as endogenous substances such as steroids (Xie et al, 2003), heme and bilirubin (Xie et al, 2003), thyroid hormone (Maglich et al, 2004), and cholesterol/bile acids (Guo et al, 2003; Stedman et al, 2005). CAR’s function has also emerged as an important regulator of lipid and energy metabolism (Wada et al, 2009) and as a modulator of genes involved in a diverse array of physiological processes that include cell growth and differentiation (Page et al, 2007; Liu et al, 2009; Baskin-Bey et al, 2006; Blanco-Bose et al, 2008). …”
Section: Introductionmentioning
confidence: 99%